2021
DOI: 10.3390/pathogens10121606
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcal Colonization in African Countries: Prevalence, Capsular Serotypes, and Molecular Sequence Types

Abstract: Streptococcus agalactiae or group B streptococcus (GBS) is a commensal of the gastrointestinal and genitourinary tracts of healthy women and an important cause of neonatal invasive infections worldwide. Transmission of bacteria to the newborn occurs at birth and can be prevented by intrapartum antibiotic prophylaxis. However, this not available in resource limited settings in Africa, which carries a particular high burden of disease. Serotype based vaccines are in development and present a suitable alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…All statistical analyses between clinical data and microbiology findings are exploratory and hypothesis forming. Group B Streptococci (GBS), considered the dominant cause of sepsis in high-income countries [ 47 , 72 ], was not found/reported, and this has also been observed in other studies [ 1 , 5 , 6 , 8 , 60 , 73 ]. With limited microbiology resources in many LMICs however (GBS require additional media and growth requirements), septic neonates may be deceased prior to a blood culture and Vera et al ., suggest GBS are perhaps underreported due to these infections presenting very early into life [ 47 ].…”
Section: Discussionmentioning
confidence: 72%
“…All statistical analyses between clinical data and microbiology findings are exploratory and hypothesis forming. Group B Streptococci (GBS), considered the dominant cause of sepsis in high-income countries [ 47 , 72 ], was not found/reported, and this has also been observed in other studies [ 1 , 5 , 6 , 8 , 60 , 73 ]. With limited microbiology resources in many LMICs however (GBS require additional media and growth requirements), septic neonates may be deceased prior to a blood culture and Vera et al ., suggest GBS are perhaps underreported due to these infections presenting very early into life [ 47 ].…”
Section: Discussionmentioning
confidence: 72%
“…Notably, previous studies have shown that the fve serotypes of S. agalactiae (Ia, Ib, III, IV, and IX) are pathogenic and cause high mortality in other fsh species [15,22,24,32,36,[38][39][40]. Interestingly, although S. agalactiae serotype VII has not been reported to cause disease in fsh, previous reports have described this serotype in humans in Southern Ghana, West Africa, Malaysia, Iran, and Bangladesh [41][42][43][44][45]. Additional characterisation of the bacteria using PFGE analysis confrmed S. agalactiae serotype VII in the moribund snakeskin gourami, which is distinct from the S. agalactiae serotype III isolated from tilapia and red tilapia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found regional and ethnic variations in the incidence of GBS infection and serotype and genotype distribution in pregnant women. 1 , 19 , 20 In pregnant women, different GBS serotypes and genotypes have different levels of pathogenicity and are associated with different levels of risk of neonatal GBS-EOD. 21 Therefore, knowledge of the serotypes, genotypes, virulence factors, and drug-resistance profiles of GBS strains in a region could help clinicians to identify high-risk pregnant women and infants for monitoring and treatment, and benefit the development of specific GBS vaccines.…”
Section: Introductionmentioning
confidence: 99%